Virtual Biostats Day: An Interactive Online Biostatistics Outreach Program Directed at High School Students in Groups Historically Underrepresented in STEM Careers - Esther Drill; Jessica A. Lavery; Stephanie Lobaugh; Jessica Flynn; Samantha Brown; Hannah Kalvin; Joanne F. Chou; David Nemirovsky; Zoe Guan; Sujata Patil; Kay See Tan (Journal of Statistics and Data Science Education)
Persistent underrepresentation of Black and Hispanic Statistics degree holders relative to the U.S. population occurs at all levels in post-secondary education, contributing to the underrepresentation of Black and Hispanic Bio/Statisticians. Attempting to address this inequity before the undergraduate level, Memorial Sloan Kettering (MSK)’s Bridge to Biostats committee was established with the mission to increase awareness of and interest in the field of Biostatistics among high school students in groups underrepresented in STEM fields. We describe in this article an outreach program targeted to underrepresented students in New York City with innate aptitude and interest in STEM subjects, but minimal exposure to Statistics. Virtual Biostats Day is a 1–1/4 hr online exposure program that incorporates interactive elements exploring statistical concepts alongside clear descriptions of the field of Biostatistics and the roles and responsibilities of a Biostatistician. Students are also introduced to professional Biostatisticians who describe their journeys from high school to where they are today. This combination of didactic and active learning has engaged students, even in the online environment. We relate our experience in implementing and presenting our program to students and provide a complete toolkit for other Bio/Statistics departments or organizations interested in engaging in similar outreach work. Supplementary materials for this article are available online.